λ-Rearrangements Characterization of Pringsheim Limit Points - Richard F. Patterson (International Journal of Mathematics and Mathematical Sciences)
Sufficient conditions are given to assure that a four-dimensional matrix A will have the property that any double sequence x with finite P-limit point has- a λ-rearrangement z such that each finite P-limit point of x is a P-limit point of Az.